2015
DOI: 10.1002/pon.3849
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of a behavioral intervention for persistent urinary incontinence in prostate cancer patients

Abstract: Objective To evaluate the cost-effectiveness of a behavioral intervention for urinary incontinence of prostate cancer patients. Study subjects were either participating in or eligible but declined (i.e. nonparticipating) the active intervention study. Methods The intervention-participating subjects were randomized to three groups, including two intervention groups (support and telephone groups) and a usual care reference group. Intervention-nonparticipating subjects were concurrently enrolled. Intervention e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 25 publications
(31 reference statements)
0
32
0
Order By: Relevance
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 18 articles included, (5)(6)(7)(8)11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) 17 were found in the electronic databases and one in the references of the selected studies. In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set.…”
Section: Resultsmentioning
confidence: 99%
“…In the reference lists of the excluded reviews, no study was found that complied with the inclusion criteria set. As for the language of the articles, 16 were published in English, (5,6,8,11,12,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) one in Spanish (7) and one in Portuguese. (23) As for the country where the study was developed, three were developed in Spain, followed by the United States, United Kingdom, Italy, Australia and China, with two studies each, and Brazil, Denmark, Sweden, Norway and The Netherlands, with one study in each country.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations